(untitled) (International Journal of Nursing Education, 2026)
Nursing is increasingly recognized as a transformative force in advancing the Sustainable Development Goals (SDGs). This article analyzes nursing’s direct and indirect contributions to the SDGs highlighting the multidimensional role of nurses in health promotion, education, gender equity, environmental stewardship, economic growth, and social justice. Nurses play a pivotal role in achieving SDG 3 through preventive care, chronic disease management, emergency response, and mental health promotion, while also significantly contributing to SDGs related to education, clean water and sanitation, decent work, reduced inequalities, climate action, and strong institutions. Bibliometric evidence underscores that nursing research is heavily concentrated on health-related goals, with notable gaps in areas such as poverty reduction and zero hunger. The article further explores nursing leadership in innovation, sustainability, ethical governance, and partnerships, emphasizing the need for stronger research integration, policy engagement, and interdisciplinary collaboration. Strengthening nursing education, leadership, and research capacity is essential to maximize its impact on the 2030 Agenda. The analysis concludes that nursing is not merely a supporting discipline in global development but a central catalyst for achieving a healthier, more equitable, and sustainable future from very ancient period.